2000
DOI: 10.1182/blood.v96.6.2100.h8002100_2100_2107
|View full text |Cite
|
Sign up to set email alerts
|

Similar repopulating capacity of mitotically active and resting umbilical cord blood CD34+ cells in NOD/SCID mice

Abstract: It was hypothesized that during mammalian development, the extensive need for hematopoietic cells requires equal contribution to blood cell production from both quiescent and cycling hematopoietic stem cells (HSCs) while maintaining the stem cell pool. To investigate this hypothesis, the engraftment potential of umbilical cord blood (UCB) CD34+ cells residing in either G0(G0CD34+ cells) or G1(G1CD34+ cells) phases of the cell cycle was assessed in nonobese diabetic/severe combined immune-deficient (NOD/SCID) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…Indeed, some studies concluded that bone marrow mononuclear cells and mobilized CD34 ϩ blood cells in G 0 have a better engraftment potential than cells in other phases of the cell cycle [30,40,41]. By contrast, other studies showed no differences in engraftment capacity of CB and fetal cells, whatever their cell cycle phase [42,43], and unimpaired SRC activity of HSCs cycling actively ex vivo [44 -46]. Thus, our results could reflect the maintenance of engraftment capacity of actively proliferating SRCs at 20% of O 2 (in line with [43][44][45][46]), the loss of homing/engraftment capacity of SRCs after re-entering in G 0 at 0.1% O 2 , or the expression of genes independent of cell cycle status and involved in bone marrow homing of SRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies concluded that bone marrow mononuclear cells and mobilized CD34 ϩ blood cells in G 0 have a better engraftment potential than cells in other phases of the cell cycle [30,40,41]. By contrast, other studies showed no differences in engraftment capacity of CB and fetal cells, whatever their cell cycle phase [42,43], and unimpaired SRC activity of HSCs cycling actively ex vivo [44 -46]. Thus, our results could reflect the maintenance of engraftment capacity of actively proliferating SRCs at 20% of O 2 (in line with [43][44][45][46]), the loss of homing/engraftment capacity of SRCs after re-entering in G 0 at 0.1% O 2 , or the expression of genes independent of cell cycle status and involved in bone marrow homing of SRCs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our results in PBSC and those by Glimm & Eaves (1999) in CB and fetal liver demonstrate that the long‐term repopulating ability of primitive stem cells is not only confined to the cytokine‐non‐responsive compartment, and, moreover, this ability is not necessarily lost after mitotic activation with early‐acting growth factors. In addition, recently it has been proven that CB CD34 + cells residing in either G 0 or G 1 have similar reconstitution potential in NOD/SCID mice (Wilpshaar et al , 2000). Although our methodology can not determine the number of divisions that a group of cells has undergone, the high resolution of PKH26 dye ensured that all the cells transplanted into NOD/SCID mice were post‐mitotic, and therefore that some kind of self‐renewal occurred in our cultures with early‐acting cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The human SRC assay was performed in sublethally irradiated (300 cGy) NOD-SCID mice as described previously (48), using limiting dilution analysis (49).…”
Section: Mouse Hsc and Human Src Assaysmentioning
confidence: 99%